Neurodynamic Technique Terhadap Penurunan Nyeri, Peningkatan Grip Strength, dan Peningkatan Kemampuan Fungsional Pada Carpal Tunnel Syndrome - Arifin, Safrin; Dheanisa, Fathia (UI Scholars Hub, 2023)
Carpal tunnel syndrome is a syndrome that occurs in 1-4% of the total population worldwide. This condition causes disruption of function and motion in the wrist that spreads to the fingers. Physiotherapy intervention is necessary to reduce the severity of symptoms in patients with CTS. Neurodynamic Techniques are nerve mobilization techniques that aim to restore homeostasis in the nerves so as to reduce pain and improve functional ability. Materials and methods. This research was conducted through searching several databases, found 31 articles which were then filtered and selected as many as 10 articles. However, of the 11 articles, further screening was carried out again based on inclusion criteria. The final result after selection is 9 articles. Results. From the 9 articles that have been reviewed neurodynamic technique provides significant benefits to reduce pain and increase functional ability in patients with carpal tunnel syndrome. Conclusion. Good results can be obtained if the treatment is done regularly with a dose of 2-3 times a week as many as 3 sets of 20 repetitions per training session and accompanied by exercise therapy performed every day. Neurodynamic technique can produce a positive effect on the reduction of pain in cases of CTS so as to restore the function of motion in the wrist and fingers. Keywords: Carpal tunnel syndrome, neurodynamic technique, grip strength, functional ability